PENGGUNAAN MIKROALGA CHLORELLA PYRENOIDOSA CHICK AMOBIL UNTUK MENINGKATKAN KUALITAS AIR DALAM AKUAKULTUR - Riffiani, Rini (Jurnal Hidrosfir Indonesia, 2010)
Immobilized microalgae Chlorella pyrenoidosa was applied initially to nutrient and heavy metal removal of wastewater. Immobilized microalgae using alginate was then developed for aquaculture application, such as controlling fish water culture quality to uptake concentration of ammonium, nitrate and to increase the oxygen level in water. During immobilization, algal cell maintain their respiratory and photosynthetic activities as that cell in the normal condition. The objective of this research was to examine the role of C. pyrenoidosa immobile on controlling the water quality by measuring ammonium, nitrate, and dissolved oxygen content. Five aquariums consisted of 40 litres of water were filled with 20 Nile Tilapia (Oreothromis niloticus) with the average weight between 1.6 and 1.7 g. The immobile algae cell were packaged in two nillon porus bag (pore size was 2x3 mm in diameter) and each immobile cell had 4 millimeter in diameter. Each aquarium was added with 3000, 4000, 5000, and 6000 of immobile cell. The treatment had 2 replicates. The results showed that the aquarium filled with 4000 beads of immobile cell gave the best result. The ammonium content on the water decrease 6,626 ppm/day, nitrate content on the water decreased 13.99 ppm/ day, soluble oxygen raised 0.766 per day and fish biomass raised 1.56 g/fish for 15 days.